1998
DOI: 10.1055/s-2008-1052011
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Image-Guided Neuroendoscopy: Development and Early Clinical Experience

Abstract: Technical advances and pioneering surgeons have established neuroendoscopy as an accepted diagnostic and therapeutic tool. The clinical indications for endoscopy, variety of operative techniques and number of endoscopic surgeons continue to increase steadily. However, there are fundamental limits to the scope of freehand endoscopy principally governed by the need for direct vision of anatomical and pathological structures. In addition, whilst the expert neuroendoscopist is only occasionally disorientated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Similarly, we have yet to be convinced of the value of combining neuroendoscopy with any form of neuronavigation, something which has been advocated by some groups as contributing to safety. 34 Developments in real-time neuronavigation or robotics 35 may alter this position. Although electrodiathermy remains the most useful means of cutting and coagulating tissue the KTP laser (Laserscope, San Jose, CA, USA) has proved very promising in neuroendoscopic procedures with the opportunity for 'no contact' coagulation.…”
Section: Technical Aspectsmentioning
confidence: 98%
“…Similarly, we have yet to be convinced of the value of combining neuroendoscopy with any form of neuronavigation, something which has been advocated by some groups as contributing to safety. 34 Developments in real-time neuronavigation or robotics 35 may alter this position. Although electrodiathermy remains the most useful means of cutting and coagulating tissue the KTP laser (Laserscope, San Jose, CA, USA) has proved very promising in neuroendoscopic procedures with the opportunity for 'no contact' coagulation.…”
Section: Technical Aspectsmentioning
confidence: 98%
“…8,10,15,31,32,35,37 However, the role of image guidance in endoscopic procedures remains to be determined. Based on our experience in 255 intracranial endoscopic procedures, including 148 third ventriculostomies, we found that for most endoscopic procedures in hydrocephalic ventricles, a free-hand approach is adequate.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic route from burr hole via the foramen of Monro to the third ventricular floor can be simulated virtually on the screen. Bony structures as target points like the dorsum sellae or the clivus can be used to overcome the potential problem of brain shift due to CSF loss, although it has been shown that, regarding deep midline structures, a relevant distortion must not be expected [24].…”
Section: Discussionmentioning
confidence: 99%